Mengungkap Fenomena Investasi: Bias Kognitif, Risk Perception, Finansial Literacy, dan Penggunaan Robo Advisor Generasi Z - Eka Yulianti; Sulaeman Rahman Nidar (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to explore the phenomenon of investment among Generation Z, focusing on cognitive biases, risk perception, financial literacy, and the use of robo-advisors. The research employs a descriptive method with a survey approach using questionnaires as the primary instrument. The population of this study consists of Generation Z investors in West Java, selected through convenience sampling techniques. The findings indicate that out of 146 respondents, there is a notable presence of cognitive biases, accompanied by low-risk perception and good financial literacy. However, only 28% of respondents utilize robo-advisors, with investment decisions that tend to be irrational. The study concludes that although respondents demonstrate good financial knowledge, they still make errors in investment decision-making. Keywords: Disposition Bias, Financial Literacy, Herding, Investment Decision, Risk Perception, Robo Advisor.